Case-Based Interactive E-Module: an Alternative Supplement to Increase Student Learning Motivation - Kusumantoro; Jaenudin, Ahmad; Sari Melati, Inaya (Journal of Education Technology, 2022)
Learning is designed to increase student participation in the learning process by presenting real problems to be solved by students. This study aims to identify the feasibility and effectiveness of using an interactive e-module based on the case method in increasing student learning motivation. This type of research is development. The method used in developing the product is ADDIE. Data collection techniques using questionnaires, interviews, observation, and pretest-posttest results. The instrument used to collect data is a questionnaire. Data analysis techniques using parametric statistics with paired sample t-test and independent t-test. The assessment results by experts show that the interactive e-module based on the case method is feasible to use in the learning process. The results of statistical tests show that H1 is accepted, so there is a significant difference in the average student learning motivation between the experimental and control classes. Thus, the case method-based interactive e-module has been confirmed to be effective in teaching Microeconomics and can be developed for other courses with some technical adjustments.